The Role of Multicultural-Based Civic Education Learning in Developing Tolerance among Elementary School Students: A Systematic Literature Review - Gede Riyan Sedana Putra; Dewa Bagus Sanjaya; I Nengah Suastika (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study analyzes the role of multicultural-based Civic Education in developing tolerance among elementary school students through a Systematic Literature Review. The topic is relevant because Indonesia’s ethnic, religious, cultural, and linguistic diversity requires education that builds mutual respect from an early age. This review synthesized 15 selected journal articles related to multicultural education, Civic Education, tolerance, diversity, and multicultural awareness in elementary school contexts. The data were analyzed using thematic synthesis. The findings show that multicultural-based Civic Education supports tolerance development in three main ways. First, multicultural values are integrated through lesson planning, diversity materials, discussion, simulation, and contextual learning activities. Second, participatory, dialogical, and collaborative learning strategies encourage empathy, tolerance, and respect for differences. Third, implementation success depends on teacher competence, school support, learning resources, and family and community involvement. The review also found that previous studies remain fragmented across multicultural awareness, character education, and learning strategies. Therefore, multicultural-based Civic Education is a relevant and contextual approach to strengthening tolerance among elementary school students in diverse learning environments.